Prediksi Aktivitas Antikanker Payudara Senyawa Fevicordin dari Biji Phaleria macrocarpa (Scheff) Boerl. pada ERƒÑ Melalui Hubungan Kuantitatif Struktur dan Aktivitas metode Multiple Linear Regression Analysis dan Partial Component Analysis - Muchtaridi -; A. Mutalib -; Jutti Levita -; A. Diantini -; Ida Musfiroh - (Bionatura, 2011)
In this study fevicordin is proposed to be used for anti breast-cancer. The development of this compound was based on Quantitative Structure Activity Relationship (QSAR) study of 37 estrogen analogues using MLRA (Multiple Linier Regression Analysis) and PCA (Partial Component Analysis). QSAR equations resulted from MLRA and PCA techniques are:Log Ki = -16.5348 + 9.4000 Ovalitas - 0.0472 Molar Volume - 1.3985 Dipole Energy + 0.4891 Dipole Length + 0.0000 Torsion Energy + 0.0113 Total Areaand Log Ki = -16.8273 – 1.4970 Homo – 0.0214 Area Polar + 0.4940 Dipol – 0.0131 Total Area, respectively.The models were used to predict fevicordin’s Ki value, which had been studied using radioligand binding assay by Nakata and his colleagues, and resulted 6.13-15M (in Tris buffer using 3H-estradiol as competitor) and 2.60.10-14M (in Hepes buffer using [125I]estradiol as competitor), respectively.Keywords : Fevicordin, Breast cancer, ERá, Ki, QSAR